Proceedings of the 2014 ACM SIGMOD International Conference on Management of Data 2014
DOI: 10.1145/2588555.2610524
|View full text |Cite
|
Sign up to set email alerts
|

Answering top-k representative queries on graph databases

Abstract: Given a function that classifies a data object as relevant or irrelevant, we consider the task of selecting k objects that best represent all relevant objects in the underlying database. This problem occurs naturally when analysts want to familiarize themselves with the relevant objects in a database using a small set of k exemplars. In this paper, we solve the problem of top-k representative queries on graph databases. While graph databases model a wide range of scientific data, solving the problem in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Top-k diversification. There exist several studies on the top-k graph diversification [5,10,12,13,21,22,[29][30][31]. Qin et al [21] investigate the diversified top-k search results in a graph.…”
Section: Related Workmentioning
confidence: 99%
“…Top-k diversification. There exist several studies on the top-k graph diversification [5,10,12,13,21,22,[29][30][31]. Qin et al [21] investigate the diversified top-k search results in a graph.…”
Section: Related Workmentioning
confidence: 99%
“…For subgraph searching, a large number of index-based graph matching and searching frameworks have been proposed including gIndex [7], TreePi [9], FG-index [11], NB-index [22], LW-index [23], Tree+D [8], GCode [13], GPTree [24], Closure-tree [12], Turboiso [25], SODA [26], SING [27], and GiS [15]. These graph-indexing approaches have been designed mainly for performing subgraph querying from a graph database consisting of many small-or medium-sized graphs.…”
Section: Related Workmentioning
confidence: 99%
“…DisC computes the smallest set of relevant objects that represents all of the relevant objects in the database. A budget-constrained model to maximize the representative power was first studied in [5] with a specific focus on graph databases. Authors in [5] showed that the information density of an answer set is inversely proportional to the budget.…”
Section: Related Workmentioning
confidence: 99%